2013
DOI: 10.1002/poc.3104
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidising activity of cinnamic acid derivatives against oxidative stress induced by oxidising radicals

Abstract: Cinnamic acid and its derivatives react with hydroxyl radical (HO ), in neutral medium, to give hydroxylation products, whether on the benzene ring or on the exocyclic chain, and decarboxylation products. The latter compounds are also obtained after oxidation of the same substrates by the SO 4 À radical anion. Evidence was provided for the protecting effects afforded by cinnamic acid and hydroxylated derivatives against oxidative reaction mediated by HO . By using adenine as a model compound, the results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…In practice, CO2 volumes equivalent to 9% of the total expected carbon were measured over three hours in the deoxygenated conditions, which, allowing for dissolution, is within a reasonable margin of error. It should be noted that the concentrations of 3 detected in our experiments do not match the amounts predicted if all of the CA was converted via this route but the difference can be attributed to some simultaneous degradation of 3 (via oxygen free routes in contrast to the reaction described in Scheme 2) and competition with hydroxylation of the aromatic ring which Santos et al 26 identified as a significant route for the reaction of cinnamic acid with hydroxyl radicals generated by gamma radiolysis.…”
Section: The Mechanism Of the Photocatalytic Decomposition Of Cinnamic Acidcontrasting
confidence: 85%
See 1 more Smart Citation
“…In practice, CO2 volumes equivalent to 9% of the total expected carbon were measured over three hours in the deoxygenated conditions, which, allowing for dissolution, is within a reasonable margin of error. It should be noted that the concentrations of 3 detected in our experiments do not match the amounts predicted if all of the CA was converted via this route but the difference can be attributed to some simultaneous degradation of 3 (via oxygen free routes in contrast to the reaction described in Scheme 2) and competition with hydroxylation of the aromatic ring which Santos et al 26 identified as a significant route for the reaction of cinnamic acid with hydroxyl radicals generated by gamma radiolysis.…”
Section: The Mechanism Of the Photocatalytic Decomposition Of Cinnamic Acidcontrasting
confidence: 85%
“…Scheme 3, for example shows competing pathways to products 2 and 3 arising from attack by the hydroxyl radical on different sides of the exocyclic C=C. Hydroxylation of the position α to the carboxylic acid moiety then leads to decarboxylation to a styryl alcohol that tautomerises to product 3, as suggested by Santos et al 26 Alternatively, hydroxylation at the other side of the double bond followed by attachment of oxygen or superoxide at the radical centre and a reverse-aldol reaction cleaving the C-C bond gives 2 and O=CH-CO2H. Note too, that the order of hydroxylation and dioxygen attack could be reversed and still give 2.…”
Section: The Mechanism Of the Photocatalytic Decomposition Of Cinnamic Acidmentioning
confidence: 88%
“…Trans-2,3-dihydroxycinnamate is a derivative of cinnamic acid, which is an intermediate in the biosynthesis of lignin, flavonoids, and other secondary metabolites produced by plants like C. sativa (87). Cinnamic acid and its derivatives, like trans-2,3-dihydroxycinnamate, possess antioxidizing activity (88). Vanillic acid is a dihydroxybenzoic acid derivative commonly used as a flavoring agent.…”
Section: Hydroxycinnamic Acid Derivativesmentioning
confidence: 99%
“…• OH-mediated reaction pathways. Hydroxylation at the other side of the double bond of cinnamic acid, followed by attaching the superoxide or oxygen at the radical center and a reverse-aldol reaction cleaving the C−C bond, produces benzaldehyde as well as O=CH−CO 2 H; this has been documented as an important pathway for the reaction of • OH with cinnamic acid (Santos and Vieira 2013). Benzaldehyde is a reactive chemical (Jin et al 1998), which exhibits bioreactive toxicity to increase the overall toxicity of the system.…”
Section: The Photochemical Degradation Mechanismmentioning
confidence: 99%